Allosteric regulation of rhomboid intramembrane proteolysis. (9th July 2014) - Arutyunova, Elena; Panwar, Pankaj; Skiba, Pauline M; Gale, Nicola; Mak, Michelle W; Lemieux, M Joanne
<x xml:space="preserve">Abstract</x> Homotropic allosteric communication between rhomboid dimers controls efficient cleavage of cognate transmembrane substrate while being dispensable for proteolysis of generic soluble substrates. <boxed-text content-type="graphic" id="embj201488149-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>